The role of the municipalities in achieving the EU’s sustainable energy transition - Takácsné Papp, Adrienn (Észak-magyarországi Stratégiai Füzetek, 2023)
Greenhouse gas emissions are clearly responsible for the intensification of climate change, the largest share of which can be attributed to energy production and use. The European Union aims to reduce its greenhouse gas emissions to net zero by 2050. This energy transition by 2050 is called the energy transition. One of the European Union's best-known energy and climate organisations is the Covenant of Mayors for Climate and Energy (CoM). This publication evaluates the role of municipalities in the energy transition with the help of the analysis of the Sustainable Energy and Climate Action Plans (SECAP) document prepared by the Hungarian municipalities joining the alliance, especially from 16 submitted cities point of view. When planning the area-by area reductions formulated in their mitigation action plans, they realistically perceive the extent of their direct intervention opportunities, they expect a greater proportion of the planned measures from local actors, so they can help achieve the goals by their exemplary operation, organizing awareness-raising events and finding sources of funding. Through their indirect role in local energy management, municipalities are important actors in achieving the EU's energy transition.